Numerical investigation of coupled mass transport and electrochemical reactions in porous SOFC anode microstructure. (June 2017) - Xu, Han; Dang, Zheng
Graphical abstract: Highlights: Pore-scale LB model is built for coupled transport and reactions in porous anode. The coupled interaction of mass transport and electrochemical reactions is studied. Effect of anode microstructure heterogeneity is studied quantitatively. Effects of operating parameters on coupled processes are discussed at pore scale. Abstract: To investigate the coupled mass transport and electrochemical reactions in porous anode of solid oxide fuel cell (SOFC), a pore scale model employing the multi-component Lattice Boltzmann (LB) model for mass transport in the pore phase and a six-step reaction for electrochemical reactions at three phase boundaries is established. This model is superior in including the effects of heterogeneity of anode microstructure, making it qualified to quantitatively simulate local distributions of various physical fields without dependence on any statistical parameters. The characteristics of coupled interactions of mass transport and electrochemical reaction are analyzed visually by comparing H2 molar fraction distributions within the pore phase of the anode. It is demonstrated that, for anodes with different heterogeneous microstructures but with same porosity and tortuosity factor, the mass transport and electrochemical reaction process can be quite different, even under the same boundary conditions. Meanwhile, based on the same anode microstructure, species molar fraction varies similarly along the primary transport direction, even though the operating conditions are quite different. Besides, the influences of fuel composition, activation overpotential and operating temperature are also discussed at pore scale by the present model.